Responses to Cyber Terrorism - Centre of Excellence Defence Against Terrorism, Turkey Ankara (IOS Press, 2013)
The development of the internet is much more than a story of technological achievement: it is about social change. It is not only a history of the accessibility of interconnected computers and user-friendly software, but also of a technological revolution. The internet has enabled the democratisation of information sources away from the elites of the mass media and institutionalised politics into the hands of active, assessing audiences. This paper will address both the technological and social change that the internet has brought about. It will describe a brief history of technological development of what is now readily known as the internet, including some of the more popular software applications associated with it. I will then briefly look at the main issues of social interaction on internet platforms and how information sources have changed. Finally, I shall make some observations on what the future of the internet may be